Job Security and the Age-Composition of Employment: Evidence from Chile - Pagés, Carmen (Estudios de Economía, 2016)
This paper develops and tests a mechanism by which job security affects theage-composition of employment. This mechanism is based on the relative costsof dismissing young versus older workers resulting from job security provisionsthat are related to tenure. Using 39 consecutive annual household-surveys fromChile, we find that job security is associated with a substantial decline in thewage employment-to-population rate of young workers. In contrast, we do notfind such a decline in young self-employment rates or in the wage employmentrates of older workers. Comparing results for men and women and using measuresof relative dismissal costs, we find that the adverse effect of job securityon youth employment is driven by the link between severance payments andtenure. We also find that job security does not have a significant impact onoverall aggregate employment, participation or unemployment rates.